Anthro-Vision : How Anthropology can Explain Business and Life - Tett, Gillian (London Random House Business, 2021)
A revelatory model that explains how we buy, sell, work and live. For over a century, anthropologists have immersed themselves in unfamiliar cultures, uncovering the hidden rituals that govern how people act. Now, a new generation of anthropologists are using these methods in a different context, to illuminate the behaviour of consumers and businesses at home. In Anthro-Vision, Gillian Tett - bestselling author, Financial Times journalist, and anthropology PhD, reveals how anthropology can make sense of people's behaviour, in business and beyond. She outlines how anthropology helps explain consumer habits, revealing the 'webs of meaning' that underpin how we shop, and unpicking the subtle cultural shifts driving the rise of green investment. She explores how anthropology can shed light on the workplace, identifying the hidden tribes within the office, and pinpointing which rituals are binding together a team. And she shows how we can all use anthropology in our own lives, too- helping us make better decisions, navigate risk - even work out what our peers are really thinking. Along the way, Tett draws on stories from Tajik villages and Amazon warehouses, Japanese classrooms and Wall Street trading floors, all to reveal the power of anthropology in action. The result is a wholly new way to make sense of human behaviour. In a short-sighted world, we can all learn to see clearly - using the power of Anthro-Vision.
Include Notes, Bibliography and Index
Keywords: Teams in the workplace -- Public anthropology -- Labor--Anthropological aspects -- Anthropology--Research